CariesCare practice guide: consensus on evidence into practice (2019)
This CariesCare practice guide is derived from the International Caries Classification and Management System (ICCMS) and provides a structured update for dentists to help them deliver optimal caries care and outcomes for their patients. This '4D cycle' is a practice-building format, which both prevents and controls caries and can engage patients as long-term health partners with their practice. CariesCare International (CCI™) promotes a patient-centred, risk-based approach to caries management designed for dental practice. This comprises a health outcomes-focused system that aims to maintain oral health and preserve tooth structure in the long-term. It guides the dental team through a four-step process (4D system), leading to personalised interventions: 1st D: Determine Caries Risk; 2nd D: Detect lesions, stage their severity and assess their activity status; 3rd D: Decide on the most appropriate care plan for the specific patient at that time; and then, finally, 4th D: Do the preventive and tooth-preserving care which is needed (including risk-appropriate preventive care; control of initial non-cavitated lesions; and conservative restorative treatment of deep dentinal and cavitated caries lesions). CariesCare International has designed this practice-friendly consensus guide to summarise best practice as informed by the best available evidence. Following the guide should also increase patient satisfaction, involvement, wellbeing and value, by being less invasive and more health-focused. For the dentist it should also provide benefits at the professional and practice levels including improved medico-legal protection.